Juridical Study for Drivers who Smuggle and Embezzle Type of ll Solar Fuel Using Expedion Truck in West Bangka (Case Studies PN Mentok Decion Number: 43/Pid.B/Lh.2023/PN.Mtk) - Herlina, Herlina; Riyadi, Eko; Dewi, Virna; Yuliana, Sri; Pawari, Rahmiati Ranti; Rindiani, Anis (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2024)
Fuel oil is one of the vital elements needed to serve the wider community, both in poor countries, developing countries and even in countries with developed country status. The current use of fuel oil not only has implications for a country's foreign policy which has a significant influence on the country's economic growth, but also has a global impact resulting in human suffering. The type of research used in this research is normative juridical research which examines the law of internal perspective with the object of research being legal norms. Normative legal research functions to provide juridical arguments when there is a vacuum, ambiguity and conflict of norms. This means that normative legal research plays a role in maintaining critical aspects of legal science as normative science.